2016
DOI: 10.1055/s-0042-108200
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis in Elite and Non-Elite Field Hockey Players

Abstract: Rhinitis has been demonstrated to impose a significant disease burden upon the general population. We sought to determine the prevalence of rhinitis in athletes; to investigate its relationship with co-existing allergic symptoms; and to quantify the impact of rhinitis on quality of life in the athlete.3 subgroups were studied: elite field hockey players (FHP); non-elite FHP; and a sedentary control group.Participants were asked to complete a rhinitis self-report questionnaire; the "Allergic Questionnaire for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Unfortunately, studies which satisfied the inclusion criteria did not examine the prevalence of NAR phenotype separately. Athletes are also known to suffer with exercise-induced rhinitis which is characterized by short-term rhinitic symptoms triggered by the exercise [ 29 ]. Interestingly, the prevalence of exercise-induced rhinitis was similar in between swimmers and runners [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, studies which satisfied the inclusion criteria did not examine the prevalence of NAR phenotype separately. Athletes are also known to suffer with exercise-induced rhinitis which is characterized by short-term rhinitic symptoms triggered by the exercise [ 29 ]. Interestingly, the prevalence of exercise-induced rhinitis was similar in between swimmers and runners [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Walker recently published that QOL related to nasal symptoms, as measured by the Sinonasal outcome test (SNOT) 22 questionnaire, was significantly lower in athletes compared to sedentary controls 3 and lower in athletes suffering from nasal symptoms compared to healthy athletes. 14 This questionnaire comprises 22 questions related to sinonasal symptoms as well as related functional and emotional impairment, each scored from 0 to 5 (0 = not impaired; 5 = severely impaired). Surda demonstrated that this effect was greatest in swimmers as measured by the rhinoconjunctivitis quality of life questionnaire (RQLQ).…”
Section: Impact On Quality Of Life (Qol)mentioning
confidence: 99%
“…76 However, literature suggests that athletes may not be fully aware of those regulations since several studies show that athletes with rhinitis are much less adherent to their INS compared to non-athletes; Surda showed that chronic nasal medication was significantly less taken by elite swimmers with nasal symptoms (18%) compared to symptomatic non-sporting controls (67%), 3 and Walker showed that elite hockey players were much less adherent to their INS compared to non-elite players and sedentary controls. 14 Adverse effects of INS include minor epistaxis, crusting, nasal dryness and irritation of the throat and nose; however, most of these side effects are transient and rarely require stopping INS treatment, even on a long-term base.…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study investigating field hockey players found lower Allergic Questionnaire for Athletes (AQUA) scores in elite players with rhinitis compared with nonelite players and controls with rhinitis, thus, suggesting (without immunoglobulin E [IgE] detection methods) a nonallergic cause of the upper airway symptoms in the highly trained group. 34 The causal factors hypothesized to induce NANIR symptoms include chemical irritants (chlorination products, ozone, and other indoor or outdoor pollutants) or physical triggers (changes in temperature, humidity, or osmolality).These triggers are typically known to induce symptoms in patients presenting with nasal hyperreactivity (NHR), 35 a disease characteristic that can be present in allergic, infectious, and NANIR. 36 Some specific sports seem to increase the risk for NAR, including winter sports (likely due to continuous exposure to cold dry air) and swimming (likely due to chronic exposure to chlorine and chlorination byproducts).…”
Section: Nonallergic/noninfectious Rhinitis and Exercise-induced Rhinitis In Athletesmentioning
confidence: 99%